Representation Of Librarian And Library Users In The Movie "Heartbreak Library" - Surya Ningsih Wijaya Sitompul; Abdul Karim Batubara (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
Film serves as a medium that effectively conveys topics or messages in a widespread yet accessible manner, ensuring ease of comprehension for its audience. "Heartbreak Library," in particular, addresses the predicament of Eun Soo (Kim Eugene), a librarian who apprehends a man named Kim Joon Oh (Lee Dong Wook) for his disruptive behavior towards books. The central research focus revolves around the attitudes of both library users and librarians. This study aims to analyze the portrayal of the library, delving into the depictions of librarians and patrons within the film. Employing a qualitative research approach, this investigation utilizes Roland Barthes' semiotic analysis method. The findings reveal that the librarian's demeanor adheres to professional standards, whereas some library users exhibit a lack of familiarity with library regulations, engaging in practices such as tearing books, hiding them on shelves, and causing disturbances within the library environment.